M. HEIDEGGERIS IR PAGRINDINĖS FENOMENOLOGIJOS PROBLEMOS: ONTOLOGINIS SKIRTUMAS. - Saldukaitytė, Jolanta (Problems / Problemos, 2009)
The paper deals with the problem of ontological difference in the phenomenological context. the tradition of metaphysics was thinking in the perspective of the distinction between being and beings, but the difference itself wasn't thematized. According to Heidegger, the only problem of philosophy is being itself, so the question of being must be asked again, together with the unthought ontological difference. Firstly, Heidegger analyzes the problem of the ontological difference in terms of Kant, focusing on his thesis that being is not a real predicate. Then, the article demonstrates how explaining the problem of ontological difference is related to the conception of Dasein, the meaning of being, beings, and time. Dasein is a special being who knows the difference between being and beings. But the difference may be explained only if we know the meaning of being itself and the meaning of being of beings. Analysis shows that the meaning of being is seen as temporality. Temporality is also a condition of the ontological difference between being and beings as well.